Jenis - Jenis Serangga Yang Tertarik Dengan Warna Di Kebun Melon (Cucumis melo L.) - Sari Damayanti; Dian Mutiara; Yunita Panca Putri (Universitas PGRI Palembang, 2023)
Research on the Order of Diptera on Melon Plant (Cucumis melo L.) was conducted in April - May 2022.”The purpose of the study was to examine the interest of insects in melon plants to various colors in the agrotorism of the Kenten Laut melon garden. This study uses a purposive sampling method, namely by color traps using 4 colors, namely, yellow, green,blue, and red. Observation parameters include the number of insects contained in each trap, color and type of head, mouth apparatus, limbs, antennae, and wings. The results obtained 70 insects fromthe order Diptera. The types of insects found were, Bactrocera dorsalis., Lucilia sp.,”Hermetia illucens, Musca domestica., the insects collected had different morphological types.